SUN-217 Alternate Pathways of Testosterone Action in Testis - Talapatra, Arpita (J Endocr Soc, 2019)
Declining birth rate in developing countries is a significant social complication. Male infertility accounts for 40 to 50% of human infertility, affecting 6 to 10% all males. Humans are exposed to hazardous chemicals resulting in Leydig cell and Sertoli cell dysfunction due to low level of androgen and disabled germ cell development during spermatogenesis. Testosterone is a known requirement for spermatogenesis maintenance but a direct mode of action on germ cells remains to be fully investigated. We injected ethylene dimethane sulfonate (EDS) in male rats which ablates mature Leydig cells, thus, eliminating endogenous testosterone. Testosterone loss compromises the blood-testis-barrier (BTB) integrity and decreased anchoring junction proteins. Nuclear androgen receptors (nARs) were identified in Sertoli & myoid cell nuclei and stripped cytoplasm from spermatids but not on germ cells which constitute 80% of the cell population in testis. Testosterone is present in high concentration in testis and may act either through canonical or non-canonical mechanisms. Non-canonical pathways of testosterone actions include interactions with membrane receptors and influencing other cellular functions and differing from the canonical pathway by activating nuclear receptors and influencing gene regulation. Progesterone, a steroid hormone mainly studied in female reproduction, focuses on nuclear receptors (nPRs) but can also change ion influx and intracellular Ca2+ along with other second messengers of non-genomic pathway mediated by membrane progesterone receptors (mPRs). We have initiated studies to find and characterize mRNAs for mPRs & membrane progesterone/ adiponectin receptors (mPAQRs) by RT-qPCR. These mPAQRs have structural similarity to adiponectin receptors that bind adiponectins from fat cells. We have found 5 mPRs mRNAs (mPRα, mPRβ, mPRγ, mPRδ, mPRε) expressed in testes but we do not know the cells of origin since total RNA from whole testes was used. Levels of mPRs were evaluated and significant increases in vehicle controls for mPRβ (6 fold) and mPRβ with testosterone supplementation was elevated and additional 4 fold. Understanding the levels of mPRs (mPAQRs) in specific germ cells dependent upon higher levels of testosterone for their maintenance can suggest potentially new way of associating links between higher levels of testosterone needed for maintenance of spermatogenesis and receptors other than nuclear receptors.